“Men bara att hon lyssnade betyder så mycket” En reflexiv tematisk analys av ungdomars upplevelse av att leva med postcovid - Dreifaldt,Johan; Åkesson,Elin (2025)
Many patients recover from a COVID-19 infection but some develop long lasting symptoms, which severeness has an impact on their daily function. This condition is now known as post-COVID. Studies have been conducted on adults' experiences of living with post-COVID, however little is known about how post-COVID impacts children. The current study therefore aimed to expand our understanding of adolescents' experiences living with post-COVID. Seven semi-structured interviews were carried out and thereafter analyzed with reflexive thematic analysis. Three overarching themes were identified: No longer being enough, Reaching out in the dark, See me, hear me, believe me. The first theme illustrate how adolescents view themselves and how their mood and different areas of their lives are impacted by the symptoms. The second theme captures how uncertain and unknown post-COVID can be for the adolescents and how they on their own and together with others try to find strategies that promote function and wellbeing. The third theme describes how the adolescents face distrust and ignorance and how that contrasts with facing trust, knowledge and being believed. The results from this study confirm prior studies’ findings regarding adolescents with post-COVID, and their parents' experience of post-COVID. This study shows that the post-COVID symptoms have a big impact on the adolescents experience everyday life and furthermore highlights the need for trust which can pave the way for adaptations and interventions which alleviate the symptoms in this unpredictable condition.
Keywords: postinfektiösa tillstånd; resiliens; utvecklingspsykologi; post-infectious syndrome; resilience; developmental psychology